2022
DOI: 10.6026/97320630018908
|View full text |Cite
|
Sign up to set email alerts
|

Post acute CoViD-19 syndrome (PACS) - Long CoViD

Abstract: Patients sero-positive for the Systemic Acute Respiratory Syndrome Corona virus2 (SARS-CoV2) virus develop the Corona Virus Disease 2019 (CoViD-19). CoViD-19 may be asymptomatic in some individuals, proffer mild symptoms in other patients, and can be a serious and even lethal disease in a sub-group of the population. The variables that determine the severity of CoViD-19 have not been fully characterized. What is clear is that the patients who survive CoViD-19 return to a state of sero-negativity for SARS-CoV2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…However, in a related research synthesis protocol involving three randomized controlled trials and 356 subjects, D3 supplementation was conclusively shown to improve COVID-19 severity outcomes [28] . The role of D3 in the onset and course of the Post Acute CoVID-19 Syndrome (PACS; i.e., Long COVID) [29] is yet to be determined.…”
Section: Climate Change Threats To Healthmentioning
confidence: 99%
“…However, in a related research synthesis protocol involving three randomized controlled trials and 356 subjects, D3 supplementation was conclusively shown to improve COVID-19 severity outcomes [28] . The role of D3 in the onset and course of the Post Acute CoVID-19 Syndrome (PACS; i.e., Long COVID) [29] is yet to be determined.…”
Section: Climate Change Threats To Healthmentioning
confidence: 99%
“…The following scheme reflecting multiple organ damage caused by coronavirus and leading to long COVID-19 is proposed (Chippa et al, 2022) (Fig. 1).…”
Section: Pathogenesis Of Long Covid-19mentioning
confidence: 99%
“…The terms post-acute sequelae of SARS-CoV-2 infection (PASC) and post acute COVID-19 (2.PASC) (Rubin, 2020), as well as long-haulers COVID-19, are rarely used. Consequently, long COVID-19 can be presented as a complex of different clinical symptoms in patients who were considered recovered from COVID-19 that can appear at least four weeks after the initial infection (Chippa et al, 2022). It should be noted that post-acute or long COVID is an increasingly common syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Post-COVID sequelae can occur as a continuation of the acute phase or can present later as a delayed complication of the acute phase. These symptoms can overlap with the acute phase and include fatigue, dyspnea, fevers, cough, myalgias, etc [2]. Though the exact mechanism of this post-acute phenomenon is not completely understood, it is thought to be a result of an overwhelming immune response followed by a potentially prolonged compensatory counterbalancing anti-inflammatory cascade [2].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms can overlap with the acute phase and include fatigue, dyspnea, fevers, cough, myalgias, etc [2]. Though the exact mechanism of this post-acute phenomenon is not completely understood, it is thought to be a result of an overwhelming immune response followed by a potentially prolonged compensatory counterbalancing anti-inflammatory cascade [2]. This immune system activation and suppression can result in a large toll on the body responsible for many symptoms experienced by patients in the post-acute phase.…”
Section: Introductionmentioning
confidence: 99%